NON-LINEAR RECEIVER REACTION OF IRRADIATION WITH COMPLEX SPECTRAL COMPOSITION: NON-LINEAR RECEIVER REACTION OF IRRADIATION WITH COMPLEX SPECTRAL COMPOSITION - Zhekov, Zhivko; Mardirossian, Garo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
One of the basic problems in elaboration of spectro-photometer for atmospheric ozone exploration at the Space Research Institute - Bulgarian Academy of Sciences seems to be the necessity of calculation of output signal of the irradiating receiver by fixed spectral composition and intensity. The calculation wouldn’t be difficult if the intensity values range is situated on the linear part of the irradiating receiver energetic characteristic. To the end, the absolutely spectral characteristic of receiver sensibility and spectral density of the treated receiver intensity has to be known. The paper is dedicated to the elaboration and the obtained results by offering and creating a method for definition the non-linear irradiating receiver output signal by fixed spectral composition and intensity. In the paper the obtained schemes and equations in the process of elaboration are presented characterizing the reaction of the photo-receiver complex spectral composition with nonlinear energetic characteristic.